Study on the Relationship between Chlorite Clay Film Diagenesis and Sedimentary Facies in Reservoir Sandstones. (24th March 2022) - Zhang, Rui; Qin, Guangsheng; Nie, Minglong
Abstract : A large amount of oil and gas has been found in Chang 6 Formation sandstones in Huaqing region of Ordos Basin. It is controversial whether the chlorite clay film is one of the main controlling factors of high quality sandstone reservoirs in this area. On the basis of previous studies, the chlorite clay film in sandstone reservoirs in the working area was studied by X-ray diffraction, casting thin section, scanning electron microscope, energy spectrum, and other analytical methods. The results show that the sandstones developed by chlorite clay films are closely related to the strong hydrodynamic deposition condition. The formation of chlorite clay film is a gradual process, and the particle coating is mainly formed in the early stage. The material source is the Fe-bearing flocculation precipitation produced when the river enters the lake. The chlorite lining is mainly formed in the later stage, and its material source is mainly iron ions produced by the dissolution of clastic particles such as feldspar or rock debris. The chlorite clay film cannot prevent the cementation and cannot protect the intergranular pores. Therefore, the better physical properties of the sandstones with the chlorite clay film in the Chang 6 Formation of the Huaqing region are related to the petrological characteristics of the sandstone deposited under strong hydrodynamic conditions and have little relation with chlorite clay film.